HYGIENIC ANALYSIS OF WINTER NUTRITIONAL STATUS IN PATIENTS WITH TOXIC HEPATITIS - Nizom Ermatov ,; Nurillo Mamasadikov ,; Irina Ulugnazarova , (Central Asian Journal of Medicine, 2025)
Toxic hepatitis, characterized by liver damage due to exposure to hepatotoxic substances, poses significant challenges to patients’ nutritional status, particularly during winter. Seasonal factors, such as reduced sunlight exposure, limited availability of fresh produce, and decreased physical activity, exacerbate nutritional deficiencies that can impair liver function and overall health. This study aimed to analyze the winter nutritional status of patients with toxic hepatitis, evaluating dietary intake, anthropometric parameters, and biochemical markers. Findings revealed widespread deficiencies in energy, protein, and micronutrients, including vitamin D, vitamin C, and zinc. 80 patients diagnosed with toxic hepatitis, aged 30–60 years, receiving outpatient or inpatient care during the winter season. The 40% of patients consumed less than 75% of their daily energy requirements. The average daily caloric intake was 1,480 ± 320 kcal, significantly lower than the recommended 2,000–2,200 kcal for adults with liver disease. Mean protein intake was 0.6 ± 0.2 g/kg/day, below the recommended 1.0–1.5 g/kg/day for liver regeneration. 55% of patients reported limited access to protein-rich foods such as eggs, fish, and legumes. Confirmed diagnosis of toxic hepatitis, willingness to participate, and ability to provide informed consent. Presence of comorbid conditions affecting nutritional status (e.g., advanced kidney disease, malignancies, or severe metabolic disorders). Anthropometric assessments showed significant undernutrition in a substantial proportion of patients, while biochemical markers indicated compromised liver and nutritional health. The results highlight the need for tailored seasonal interventions, including dietary diversification, supplementation, and lifestyle modifications, to improve the nutritional and health outcomes of patients with toxic hepatitis during winter. These findings underscore the importance of integrating nutrition-focused care into hepatology practice.